PREVALENCE OF RECURRENT HEADACHE AMONG UNDERGRADUATE'S STUDENTS OF A FACULTY OF MEDICAL TECHNOLOGY IN DERNA CITY: A PILOT STUDY - ASHRAF S, ELZER; RAGA A, ELZAHAF (International Journal of Clinical and Biomedical Research, 2015)
Background: Headache is major common neurological disease. Headache is a worldwide health problem, and is one of most common reasons for patients to seek health advice. The aim of this to determine prevalence of recurrent headache, associated risk factors and cause of headache among students at faculty of medical technology in Derna city, Libya. Methods: This is a cross-sectional survey in faculty of medical technology, Derna, Libya using a self-administration questionnaire from March to May 2013 on sample of 150 students in the faculty of medical technology. A questionnaire was given to the students who were selected by systematic random sampling. Results: 150 questionnaires were distributed to undergraduate student in the faculty of medical technology, of which 95 were returned, giving a participation rate of 63.3%, mean age=21.2 ± 2.2 years. There were 40 (42.1%) males and 53 (55.8%) females. The prevalence of recurrent headache was estimated to be 72.6% (69/95). The higher prevalence of headache was in females. Headache was significantly common in females than in males (X2=17.9; P <0.001). Conclusion: The study shows high prevalence of recurrent headache among the students, which will affect the academic performance, and the life activities of the students. Provide entertainments services in the school are very important to reduce prevalence of headache among the students special during the exam period. KEYWORDS: Prevalence; Recurrent; Headache; Students; Libya; Derna.